Effect of strategic alliance based on port characteristic and integrated global supply chain for enhancing industrial port performance - Sirajuddin; T. Yuri Zagloel; Sunaryo (Cogent Business & Management, 2019)
This study investigates the effect of integrated global supply chains and port characteristics toward a strategic alliance, strategic Alliance on port strategies such as maritime accessibility, physical port infrastructure, integrated information technology system, and terminal handling charge, and port strategy on port performance. Data were collected through the online and direct survey from 210 respondents made up of practitioners and port experts in Indonesia. To test the model, structural equation modeling was applied by using Lisrel 8.8. The results show that integrated global supply chain and port characteristics have a positive impact on strategic alliances which, in turn, has a positive impact on the development of maritime accessibility, physical port infrastructure, integrated information technology system, and terminal handling charge. However, not all of these factors have a significant impact on: only maritime accessibility and physical port infrastructure have positive impacts while integrated information technology system and terminal handling charge have no significant impact on Port performance.
Keywords: 650; strategic alliance; port strategy; port alliance; port performance